2022
DOI: 10.1186/s13018-022-03445-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different doses of vancomycin powder in total knee and hip arthroplasty on the periprosthetic joint infection rate: a systematic review and meta-analysis

Abstract: Background Periprosthetic joint infection (PJI) following total joint arthroplasty (TJA) is a serious complication for patients. Some joint surgeons have tried to use vancomycin powder (VP) in total knee and total hip arthroplasty to prevent postoperative PJI, but its effect is still not clear. At present, there is no meta-analysis that specifically analyses the effect of different doses of vancomycin powder on the incidence of PJI. Methods We carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Similarly, Liao et al [ 43 ], published in strong favor of VP suggesting that VP has a clear effect on preventing PJI in primary TKA. The authors reported on 11292 TKA where VP was used with a Risk Ratio (RR) of 0.41 (95%CI 0.29 to 0.58, P < 0.001) when compared to cases where VP was not used.…”
Section: Current Literature For Vp In Tka and Thamentioning
confidence: 92%
“…Similarly, Liao et al [ 43 ], published in strong favor of VP suggesting that VP has a clear effect on preventing PJI in primary TKA. The authors reported on 11292 TKA where VP was used with a Risk Ratio (RR) of 0.41 (95%CI 0.29 to 0.58, P < 0.001) when compared to cases where VP was not used.…”
Section: Current Literature For Vp In Tka and Thamentioning
confidence: 92%
“…Its use in combination with vancomycin powder makes it difficult, if not impossible, to differentiate statistically between the effect of vancomycin and the effect of povidone-iodine. 46-49 Specifically, Liao et al 43 reported similar findings strongly in favour of vancomycin powder. However, 46.7% of their results related once again to studies in which it was used in combination with povidone-iodine solutions.…”
mentioning
confidence: 85%